Implementation of School-Based Quality Improvement Management at Madrasah Ibtidaiyah PERSIS, Bandung Regency - Rohaeni, Anie (The International Journal of Education Management and Sociology, 2024)
This study aims to explore the implementation of School-Based Quality Improvement Management at Madrasah Ibtidaiyah in Bandung Regency, focusing on the supporting and inhibiting factors at Madrasah Ibtidaiyah PERSIS 119, Banjaran District, Bandung Regency. The research adopts a qualitative descriptive approach from pedagogical, sociological, managerial, and theological normative perspectives. The data sources include the principal, teachers, and staff of Madrasah Ibtidaiyah PERSIS 119. Data collection techniques involve surveys, interviews, participatory observations, and documentation. The results show that the implementation of quality management in the school includes planning, organizing, execution, and supervision. Both internal and external factors play roles in supporting and hindering this process. The study highlights the need for intensified training and education to enhance quality, both in quantity and competence. Additionally, competitions reflecting the professional abilities of teachers should be encouraged and facilitated.